A LITERATURE REVIEW ON TECHNIQUES ON COLLECTING AND SAMPLING MICROMETEORITES - Mendez, Daniel Matias Rosales (Seven Editora, 2025)
Micrometeorites (MM’s) are extraterrestrial particles that are dragged to the sun via P-R light drag and are captured by the earth in the process, the estimated influx of these interplanetary dust particles is estimated to be around thirty thousand tones every year. Collection of such take place in different locations, each required a different and specific methodology that can turn out to be very expensive and logistically challenging. Thus, the necessity of finding alternative methods of micrometeorites collection arises that accommodate these high costs and complicated logistics in an efficient way. The collection of MM’s in urban areas is only recently becoming a popular among the scientific community and even though it presents some biases, its’ easy methodology allows it to be adapted in ways that can greatly maximize the efficiency of collections made in semi-urban areas relative to others collection methods. DOI: https://doi.org/10.56238/sevened2025.018-040